Heart cockle shells transmit sunlight to photosymbiotic algae using bundled fiber optic cables and condensing lenses - Dakota E. McCoy; Dale H. Burns; Elissa Klopfer; Liam K. Herndon; Babatunde Ogunlade; Jennifer A. Dionne; Sönke Johnsen (Nature Communications)
Abstract Many animals convergently evolved photosynthetic symbioses. In bivalves, giant clams (Cardiidae: Tridacninae) gape open to irradiate their symbionts, but heart cockles (Cardiidae: Fraginae) stay closed because sunlight passes through transparent windows in their shells. Here, we show that heart cockles (Corculum cardissa and spp.) use biophotonic adaptations to transmit sunlight for photosynthesis. Heart cockles transmit 11–62% of photosynthetically active radiation (mean = 31%) but only 5–28% of potentially harmful UV radiation (mean = 14%) to their symbionts. Beneath each window, microlenses condense light to penetrate more deeply into the symbiont-rich tissue. Within each window, aragonite forms narrow fibrous prisms perpendicular to the surface. These bundled “fiber optic cables” project images through the shell with a resolution of >100 lines/mm. Parameter sweeps show that the aragonite fibers’ size (~1 µm diameter), morphology (long fibers rather than plates), and orientation (along the optical c-axis) transmit more light than many other possible designs. Heart cockle shell windows are thus: (i) the first instance of fiber optic cable bundles in an organism to our knowledge; (ii) a second evolution, with epidermal cells in angiosperm plants, of condensing lenses for photosynthesis; and (iii) a photonic system that efficiently transmits useful light while protecting photosymbionts from UV radiation.